Fixed Point of Strong Duality Pseudocontractive Mappings and Applications - Baowei Liu (Abstract and Applied Analysis)
Let E be a smooth Banach space with the dual , an operator is said to be α-strong duality pseudocontractive if , for all , where α is a nonnegative constant. An element is called a duality fixed point of T if . The purpose of this paper is to introduce the definition of α-strong duality pseudocontractive mappings and to study its fixed point problem and applications for operator equation and variational inequality problems.